1988
DOI: 10.1104/pp.86.3.672
|View full text |Cite
|
Sign up to set email alerts
|

The Generation of Singlet Oxygen (1O2) by the Nitrodiphenyl Ether Herbicide Oxyfluorfen Is Independent of Photosynthesis

Abstract: The mechanism of action of the p-nitrodiphenyl ether herbicides has remained ambiguous because of conflicting reports in the literature. The diphenyl ether herbicide oxyfluorfen causes a light induced consumption of oxygen which resembles the electron acceptor reaction of paraquat. However, this reaction is not linked to the transport of electrons through photosystem I. This conclusion is based on the observation that the rate of oxygen consumption, in the presence of oxyfluorfen, does not demonstrate a first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 10 publications
(21 reference statements)
1
16
0
Order By: Relevance
“…The absorption spectrum of PPIX, with peaks in the blue, green, and red spectral regions, fits the published action spectra for these herbicides (11,12,31,32). Duke and Kenyon (7) argued that the toxic oxygen species in NDPE action is singlet oxygen and Haworth and Hess (15) recently demonstrated that singlet oxygen is the active toxic oxygen species in NDPE action. After dark incubation with the herbicide, the temperature independence of the light-induced photodestruction indicates that a photodynamic dye is responsible for the activity (17).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The absorption spectrum of PPIX, with peaks in the blue, green, and red spectral regions, fits the published action spectra for these herbicides (11,12,31,32). Duke and Kenyon (7) argued that the toxic oxygen species in NDPE action is singlet oxygen and Haworth and Hess (15) recently demonstrated that singlet oxygen is the active toxic oxygen species in NDPE action. After dark incubation with the herbicide, the temperature independence of the light-induced photodestruction indicates that a photodynamic dye is responsible for the activity (17).…”
supporting
confidence: 66%
“…Photobleaching NDPE, cyclic imide, and oxadiazole herbicides inhibit Chl synthesis (13,34,35). Furthermore, there is good evidence that photosynthetic light reactions are not required for activity of these herbicides (6,9,12,15) or accumulation of PPIX in herbicide-treated tissues (25). Photobleaching DPE herbicides were recently found to strongly inhibit protoporphyrinogen oxidase (26).…”
mentioning
confidence: 99%
“…[50][51][52] Oxyfluorfen added to isolated thylakoid membranes, in vitro, generates 1 O 2 during illumination. 42 Treatment with the protox inhibitor acifluorfen-sodium (AF-Na) in the light induced the overaccumulation of protoporphyrinogen IX that migrates out of the chloroplast to the cytoplasm where it is oxidized to Proto IX by plasma membrane bound AF-Na-insensitive protoporphyrinogen oxidase. 47,53 A part of Proto IX so generated in the plasma membrane migrates back to the chloroplast and partitions between the cytoplasm and the chloroplast.…”
Section: Formation Of Singlet Oxygen In Plantsmentioning
confidence: 99%
“…therein). In the presence of light, the accumulated protoporphyrin IX, which is now improperly compartmentalized, is unable to be utilized for further synthesis and thus reacts with oxygen to give rise to singlet oxygen (Haworth and Hess, 1988). It is thought that singlet oxygen, a form of reactive oxygen species (ROS), in turn causes lipid peroxidation, especially on membranes (Orr and Hess, 1982), damage of other cellular constituents, and eventually cell death and, thus, the herbicidal action of these chemicals (Hess, 2000).…”
mentioning
confidence: 99%